Synthesis, structural, opticaland magnetic properties of Gd co-doped ZnO:V nanoparticles. (July 2020) - El Ghoul, J.; Al-Harbi, F.F.
Abstract: In this work, we investigate structural, optical and magnetic properties of Zn0·96 V0·04 O (ZnV4 ), Zn0·92 V0.04 Gd0.04 O (ZnV4 Gd4 ) and Zn0·88 V0.04 Gd0.08 O (ZnV4 Gd8 ) nanoparticles synthesized by sol–gel. In our protocol, the water has been slowly released following an esterification reaction, then, this solution was dried under supercritical conditions of ethyl alcohol and heat treatment in air at 500 °C for 2 h. The structural properties showed that the obtained samples have a wurtzite structure with a crystallite size around 25 nm and a secondary phase has been detected, attributed to a vanadium complex. By increasing the doping concentration of Gd, the band gap energy decreased. Photoluminescence (PL) shows that doping with Gd causes the creation of some defects in the band gap of ZnO. Magnetic measurements at room temperature showed a ferromagnetic behavior after doping. Highlights: Elaboration of Gd-doped ZnO:V nanoparticles. Structural, optical and magnetic characterizations of these nanoparticles. The powder shows an average particle size of 25 nm. The photoluminescence (PL) measure shows that the doping with Gd introduces defects into the band gap of ZnO. Magnetic measurements at room temperature showed a ferromagnetic behavior after doping.